MODEL OF SATISFACTION AND CONTINUITY OF USE E-GOVERNMENT DIRECTORIATE GENERAL OF IMMIGRATION WEBSITE - ADE PRASETYO - NIM: 23414038 , DIMAS
The rapid development of Information and Communication Technology worldwide affects the use of internet-based website as a medium of information dissemination. As an illustration, the implementation of e-government in areas of governance to improve efficiency and effectiveness of information dissemation to public. Immigration website system is one of e-government implementation which is maintained by Directorate General of Immigration at the Ministry of Justice and Human Rights Republic of Indonesia. The successful implementation of egovernment not only relies on government support but also willingness of the citizens to accept, adopt, and use it in a continuous manner. This research aims to identify factors that influence user’s satisfaction and intention to continue using the immigration website system. This research also identifies the effect of system quality, information quality, service quality, perceived security of personal data information, confirmation, and perceived usefulness to user satisfaction and the effect of user satisfaction to intention of continuity using the immigration website system. The constructs used in this research are adopted from Santhanamery and Ramay (2014), Chen (2010), and Belanche et.al., (2012). Data collection is conducted to 272 respondents who have experiences in using immigration website system. By using Structural Equation Model (SEM) analysis method, this research finds that system quality, information quality, perceived usefulness, and confirmation significantly influence user’s satisfaction. On the other hand, perceived security in the treatment of private data and service quality have no influence on user’s satisfaction. The result also confirms that satisfaction significantly influences intention of continuity using immigration system.